Novel flavivirus or new lineage of West Nile virus, central Europe - Bakonyi, Tamás; Hubálek, Zdenek; Rudolf, Ivo; Nowotny, Norbert (Emerging infectious diseases, 2005)
A flavivirus (strain 97-103) was isolated from Culex pipens mosquitoes in 1997 following floods in South Moravia, Czech Republic. The strain exhibited close antigenic relationship to West Nile virus (WNV) prototype strain Eg-101 in a cross-neutralization test. In this study, mouse pathogenicity characteristics and the complete nucleotide and putative amino acid sequences of isolate 97-103, named Rabensburg virus (RabV) after a nearby Austrian city, were determined. RabV shares only 75%-77% nucleotide identity and 89%-90% amino acid identity with representative strains of WNV lineages 1 and 2. Another RabV strain (99-222) was isolated in the same location 2 years later; it showed >99% nucleotide identity to strain 97-103. Phylogenetic analyses of RabV, WNV strains, and other members of the Japanese encephalitis virus (JEV) complex clearly demonstrated that RabV is either a new (third) lineage of WNV or a novel flavivirus of the JEV group.
Keywords: RNA, Viral; organismy bez specifických patogenů; sekvence nukleotidů; RNA virová; Specific Pathogen-Free Organisms; fylogeneze; virulence; Česká republika; Phylogeny; molekulární sekvence - údaje; Amino Acid Sequence; polymerázová řetězová reakce s reverzní transkripcí; sekvenční seřazení; Virulence; Flavivirus Infections; Mice, Inbred ICR; Czech Republic; Animals, Suckling; Animals; ženské pohlaví; infekce viry z rodu Flavivirus; Flavivirus; zvířata; Reverse Transcriptase Polymerase Chain Reaction; kojená zvířata; sekvence aminokyselin; myši; myši inbrední ICR; Molecular Sequence Data; Base Sequence; Mice; Female; Sequence Alignment